2021
DOI: 10.3831/kpi.2021.24.1.24
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant, Cytotoxicity and Cytoprotective Potential of Extracts ofGrewia FlavaandGrewia BicolorBerries

Abstract: Objectives: Accumulation of cellular reactive oxygen species (ROS) leads to oxidative stress. Increased production of ROS, such as superoxide anion, or a deficiency in their clearance by antioxidant defences, mediates cellular pathology. Grewia Spp fruits are a source of bioactive compounds and have notable antioxidant activity. Although the antioxidant capacity of Grewia Spp has been studied, there is very limited evidence that links the antioxidant activities of Grewia bicolor and Grewia flava to the inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
(27 reference statements)
0
4
0
Order By: Relevance
“…Numerous studies have shown that natural antioxidants have the ability to scavenge free radicals, thereby contributing significantly to the management of oxidative pathologies [55]. Dietary antioxidants, derived from natural sources, are of particular interest because of their potential health benefits, as they can provide protection against diseases that result from oxidative stress [55][56][57].…”
Section: Antioxidant Activity Study In Vitromentioning
confidence: 99%
“…Numerous studies have shown that natural antioxidants have the ability to scavenge free radicals, thereby contributing significantly to the management of oxidative pathologies [55]. Dietary antioxidants, derived from natural sources, are of particular interest because of their potential health benefits, as they can provide protection against diseases that result from oxidative stress [55][56][57].…”
Section: Antioxidant Activity Study In Vitromentioning
confidence: 99%
“…Eleven studies investigated the antioxidant potential of the Grewia species; eight of them studied G. asiatica [1,24,[46][47][48][49][50][51], one article focused on G. optiva [27], one evaluated G. lasiocarpa [15], and one appraised both G. flava and G. biocolor [52]. The scavenging and reducing potential of various parts of the Grewia species was reported to be dose dependent.…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…In recent studies, leaves and fruits of G. asiatica were evaluated for their memory enhancer, and antitumor effects like epidermal cervical, kidney, lung, breast, and laryngeal (Paul et al 2019;Joy et al 2019). There are other species like G. flava and G.bicolor that have also been studied for cytotoxicity (Masisi et al 2021). Focus on stem or bark, the antimicrobial and cytotoxicity activities have been reported for G. lasiocarpa (Akwu et al 2020) whereas, G. asiatica stem has been studied for anti-hyperlipidemic potentials (Khatune et al 2016).…”
Section: Introductionmentioning
confidence: 99%